Monetary and Exchange Rate Policies in Colombia : Progress and Challenges - Clavijo, Sergio (IMF Working Papers; Working Paper ;, 2004)
This paper focuses on monetary and exchange rate policies in Colombia, with particular emphasis on the period 1999-2002, when flotation of the peso and inflation targeting were adopted. We argue, first, in favor of adopting "operational inflation target ranges" and, second, in favor of strengthening the current scheme of foreign exchange options. The impact of reductions in the reference rates of the Central Bank of Colombia is also assessed. We find that a lower central bank policy interest rate is likely to affect demand only if mortgage refinancing takes place. We present preliminary estimates of Taylor rules in an openeconomy framework for Colombia.